Neurological and orbital complication of acute sinusitis in pediatric patient: A case report - Alessio Volpe; Roberto Altieri; Chiara Risi; Maurizio Erra; Rosanna De Lauso; Fabio Giusto; Angela Siervo; Annamaria Cioffi; Vincenzo Casella; Giacomo Fenza (Radiology Case Reports)
Sinusitis is a common condition that can lead to various neurological complications due to the spread of infection to the intracranial and orbital regions. Fortunately, the availability of antibiotics has significantly improved the prognosis of sinusitis-associated intracranial complications. As a result, the overall incidence of neurological complications arising from sinusitis remains low. We present a rare case of a 13-year-old male who developed epidural empyema and orbital cellulitis as a complication of acute sinusitis. The patient initially exhibited signs and symptoms of orbital cellulitis, including eyelid swelling, erythema, and pain. Subsequently, the patient's condition worsened, with the development of fever and an intensifying headache. Imaging revealed an epidural empyema, necessitating urgent medical intervention. This case highlights the importance of early recognition and prompt management of sinusitis-related intracranial and orbital complications to prevent potentially life-threatening outcomes